Geomatic methods applied to the study of the front position changes of Johnsons and Hurd Glaciers, Livingston Island, Antarctica, between 1957 and 2013 - Rodríguez Cielos, Ricardo; Aguirre de Mata, Julián; Díez Galilea, Andrés; Álvarez Alonso, Marina; Rodríguez Cielos, Pedro; Navarro Valero, Francisco (Earth System Science Data, 2016)
Various geomatic measurement techniques can be efficiently combined for surveying glacier fronts. Aerial photographs and satellite images can be used to determine the position of the glacier terminus. If the glacier front is easily accessible, the classic surveys using theodolite or total station, GNSS (Global Navigation Satellite System) techniques, laser-scanner or close-range photogrammetry are possible. When the accessibility to the glacier front is difficult or impossible, close-range photogrammetry proves to be useful, inexpensive and fast. In this paper, a methodology combining photogrammetric methods and other techniques is applied to determine the calving front position of Johnsons Glacier. Images taken in 2013 with an inexpensive nonmetric digital camera are georeferenced to a global coordinate system by measuring, using GNSS techniques, support points in accessible areas close to the glacier front, from which control points in inaccessible points on the glacier surface near its calving front are determined with theodolite using the direct intersection method. The front position changes of Johnsons Glacier during the period 1957–2013, as well as those of the land-terminating fronts of Argentina, Las Palmas and Sally Rocks lobes of Hurd glacier, are determined from different geomatic techniques such as surface-based GNSS measurements, aerial photogrammetry and satellite optical imagery. This provides a set of frontal positions useful, e.g., for glacier dynamics modeling and mass balance studies. Link to the data repository: https://doi.pangaea.de/10.1594/PANGAEA.845379.